Mapping and visualizing the global research landscapes on drinking water and cancer - Shaher Zyoud; Sa’ed H. Zyoud (Discover Applied Sciences)
Abstract A growing body of epidemiologic research has examined the potential associations between contaminants in drinking water and various cancers, with a special emphasis on sources of particular concern, including arsenic, asbestos, radon, agricultural chemicals, and byproducts of hazardous waste sites. Given the potential public health implications, a bibliometric analysis of the literature in this field is warranted. This analysis aims to systematically map the progression of research on the relationship between drinking water contaminants and cancer. By identifying emerging trends and knowledge gaps, this analysis can inform future research directions and prioritize areas with the greatest potential for public health impact. In this study, we employed a bibliometric approach to analyze research on drinking water and cancer. We searched for articles in all languages published between 1939 and 2023 using the Scopus database. To ensure the precision of our search, we validated a search strategy using relevant keywords related to drinking water and cancer. The data analysis included bibliometric indicators such as the analysis of citation patterns, publication trends, and the identification of the most productive countries and institutions in this field. Finally, we used VOSviewer software (version 1.6.20) to visualize the data through network and co-occurrence analysis. This visualization helped us identify key research clusters and emerging topics within the field. A comprehensive search of the Scopus database from 1939 to 2023 yielded 11,703 articles related to drinking water and cancer. By focusing on journal articles and excluding errata and retracted documents, the data set was refined to 10,751 publications. The majority (91.06%) of these were original research articles (n = 9790), while reviews accounted for 6.49% (n = 698). The United States was the country that contributed the most articles in this field, contributing 3,268 articles (30.4%), followed by China (n = 1496; 13.9%), Japan (n = 1358; 12.6%), and India (n = 758; 7.1%). Recent research (post-2015) focuses on assessing carcinogenic pollutant risks, mainly in groundwater. In contrast, earlier studies often used animal and human models to explore the carcinogenic effects of various chemicals found in drinking water. This study offers insight into the current research on the link between contaminants in drinking water and cancer. Most of this research focuses on high-income countries, highlighting the need for more studies in low- and middle-income regions. To advance our understanding and develop effective strategies, further research is essential. This includes improving methods for detecting and measuring emerging contaminants, as well as evaluating the impact of water treatment and sanitation practices.